(untitled) (Journal of Small Business Strategy (archive only), 1995)
Evaluating organizational performance of small businesses has frequently been a neglected managerial function. When evaluation efforts have been undertaken, they have ranged from simple internal reviews to co1nplex and often costly audits conducted by independent parties. However, most individuals working in a small business rarely take the time or make the effort to undertake a comprehensive review of their business activities. To begin the process of answering the important question of how well a small business is performing, a straightforward approach that is easy to prepare and interpret on a regular basis is required. Realizing that most individuals involved with small businesses are pressed for time, an easy-to-use evaluation instrument designed to focus attention on strategic performance indicators (SPIs) has been developed. These SPIs focus attention on the primary functional areas of a business: management, marketing, and finance. Each question has been designed to help the reviewer think about the importance of strategic performance indicators to the overall success of the business.